(untitled) (Olhares, 2015)
The article deals with the incursion of Muslim Arabian women in the show business (entertainment industry) in three Maghreb countries: Algeria, Morocco and Tunis. The inclusion of women of the Maghreb in the performing arts took place in a progressive manner for social issues and by clinging to the tradition of leaving a woman excluded from male activities including theater. From the year 1930, the female artists get to express themselves before the audience. The theatrical activity undertaken by these forerunners was a favorable factor to the massive inclusion of women in theatrical arts, not only as actresses but as directors and playwrights.